Planejamento de experimento empregado na otimização de métodos analíticos para a determinação de macronutrientes, micronutrientes e elementos traço em fertilizantes minerais por espectometria atômica - Souza, Sidnei de Oliveira (2014)
In this work were applied experimental designs to the optimization of analytical methods using atomic spectrometry. Firstly, simultaneous experimental designs were applied to the optimization of two analytical methods, being the first analytical method for the simultaneous determination of macronutrients (Ca, Mg, Na and P), micronutrients (Cu, Fe, Mn and Zn) and trace elements (Al, As, Cd, Pb and V) and other for the simultaneous determination of Th and U in mineral fertilizers, both employing inductively coupled plasma optical emission spectrometry (ICP OES). The results of the analysis of mineral fertilizers showed that the elements regulated by Ministry of Agriculture, Livestock and Food Supply (Ministério da Agricultura, Pecuária e Abastecimento MAPA) were in agreement with the same, and that the high resolution ICP OES allowed to selectivity possible interfering Ca, Fe and Th in the determination of U, indicating that can be performed simultaneous determination of Th and U by technique. In the second part, univariate designs were applied to the optimization of two analytical methods using direct solid sampling (SS) and detection by high resolution continuum source graphite furnace atomic absorption spectrometry (HR-CS GF AAS), one for the determination of Cu and other for Hg in phosphate fertilizers. The results showed that simple superphosphate and triple superphosphate 2 fertilizers samples obtained concentrations of Hg above the maximum limit established by MAPA, as well showed the highest concentrations of Cu, however this is not regulated. The analytical methods proposed in this work were simple, efficient, fast, accurate and reliable for the determination of macronutrients, micronutrients and trace elements in mineral fertilizers by atomic spectrometry.